Innovation networks and the new Asian regionalism a knowledge platform on economic productivity - Brunner, Hans-Peter.; Edward Elgar Publishing (Edward Elgar Pub., 2016)
The rise of Asia, as well as the future of regional cooperation and integration (RCI) the world over, will be profoundly influenced by the challenges of slowing productivity growth, increasing economic inequalities and systemic vulnerabilities. Such structural reform issues will require RCI policies that complement domestic policy reform. This unique book explains what drives the regional economic integration of nations and their contribution to national knowledge capital. It also lays out how such beneficial integration can generate broad-based, equitable wealth in Europe and Asia. Unique in the regional economic integration literature, this comprehensive book identifies the set of drivers of integration for productivity growth. Importantly, it describes and compares the experiences of the Baltic Sea Region with Asia's use of a set of institutionalized consensual knowledge and decision tools to drive inclusive and productive growth throughout a period dominated by the global economic crisis. Original and enlightening, Innovation Networks and the New Asian Regionalism will be vital reading for academics and researchers interested in regional integration and innovation. Policy makers and practitioners in regional development and economic geography will also find it to be an invaluable resource. The rise of Asia, as well as the future of regional cooperation and integration (RCI) the world over, will be profoundly influenced by the challenges of slowing productivity growth, increasing economic inequalities and systemic vulnerabilities. Such structural reform issues will require RCI policies that complement domestic policy reform. This unique book explains what drives the regional economic integration of nations and their contribution to national knowledge capital. It also lays out how such beneficial integration can generate broad-based, equitable wealth in Europe and Asia. Unique in the regional economic integration literature, this comprehensive book identifies the set of drivers of integration for productivity growth. Importantly, it describes and compares the experiences of the Baltic Sea Region with Asia's use of a set of institutionalized consensual knowledge and decision tools to drive inclusive and productive growth throughout a period dominated by the global economic crisis. Original and enlightening, Innovation Networks and the New Asian Regionalism will be vital reading for academics and researchers interested in regional integration and innovation. Policy makers and practitioners in regional development and economic geography will also find it to be an invaluable resource.
1. The impact of regional cooperation and integration drivers on economic productivity and welfare, with particular attention to southeast Asia -- 2. The view from the Baltic Sea region -- 3. The view from the greater Mekong Subregion, association of southeast Asian nations economic community, and the Central Asia regional economic cooperation region -- 4. Roadmap to innovation and skill-based cluster ecology development initiatives.
Includes index.
Description based on print record.
Description based on online resource; title from title screen (viewed May 20, 2014).
Keywords: Industrial productivity -- Asia; Production (Economic theory); Community development -- Asia; Electronic books